The Effect Of Fair Value Accounting On Earnings Quality: A Comparative Study Among Banking And Real Estate Sectors In Jordan - Ahmed M. Mubaideen; Nur H. Laili; Nurul N. Jamil; Khairil F. Khairi (Universal Publishers - Boca Raton, Florida, USA, 2024)
Non-Indexed Publication